Sustainable innovation: A consumer perspective - Frank, B.; Herbas Torrico, B.; Schvaneveldt, S. J. (2015 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2015)
In order for innovation to become sustainable, consumers need to actually purchase innovative products and services, even when these happen to be expensive. For these cases, this study addresses a gap in the literature by developing the concept of sustainable consumer innovativeness and by seeking to understand its determinants across countries. Based on data collected from more than 3,000 consumers across five countries, this study finds that sustainable consumer innovativeness tends to be influenced negatively by female sex and savings orientation, whereas it appears to be influenced positively by income satisfaction, financial expectations, curiosity, uncertainty avoidance, and status importance. It does not seem to depend on age. While most of these effects are generally valid, their magnitude tends to differ by country. These results may enable managers of innovative firms to identify lead users and thus to improve marketing strategy during the launch phase of innovative products and services.